THE IMPACT OF ACADEMIC CAPITALISM ON THE FORMATION OF INNOVATION POLICIES IN HIGHER EDUCATION AND SCIENCE - Oleksandr Romanovskyi; Yuliia Romanovska; Oleksandra Romanovska (Baltic Journal of Economic Studies, 2021)
Innovation policy in the field of higher education and science is one of the main components of the state socio-economic policy of social development and is aimed at creating favorable conditions for the market launch of new ideas created in this sphere. The purpose of the study is to analyze the decisive influence of academic capitalism on the formation of innovation policy in higher education and science, contributing to the creation of an innovative environment for transformational change in this sphere. The methodology of the research is based on an objective standardized approach to the analysis of factual data on the development and implementation of innovation policy in higher education systems and leading universities of the world, the latest published results of experiments, materials of scientific literature on innovation policy and innovation management. Research results. The main directions of innovation policy of entrepreneurial university and innovation relations in the sphere of higher education and science are investigated. It is shown that innovative transformations in the sphere of higher education and science, as a rule, take place within the framework of the innovative policy determined by the leaders of this sphere. It is noted that innovation policy in higher education is a link between the policy of research and scientific (scientific and technical) activities, search and dissemination of knowledge, education and training of qualified specialists in the field of technological development, industrial policy and environmental policy. The authors studied the following: the types of activities promoted by innovation in higher education and innovative environment of this activity; the main directions and main components of innovative policy of entrepreneurial university; innovative relations in higher education and science; innovative environment; the importance of having the necessary competencies, their formation and development; internal and external sources of competencies for universities, etc. Practical implications. The authors suggest that innovation policy in higher education is a link between the policy of research and scientific (scientific and technical) activities; search and dissemination of knowledge; education and training of qualified specialists – on the one hand, and technological development; industrial policy and environmental policy – on the other. This can be used in the creation of the theory and practice of innovation policy development in higher education. The article as a whole is devoted to the further development of the theoretical foundations of higher education innovatics.